Incidence and Outcomes of Brucella Endocarditis in a High-Prevalence Area: A Single-Center Study - Shufang Pan; Yunyue Zhao; Kaixiang Zhou; Shuru Chen; Miriban Maimaitiming; Jing Wu; Maimaitiaili Tuerxun; Yutian Chong; Jianyun Zhu (Springer, 2024)
Abstract Objective To analyze the clinical characteristics of Brucella endocarditis (BE) and observe the factors related to death to provide guidance for clinical treatment. Methods This study examined all patients with BE admitted to The First People's Hospital of Kashi Prefecture between January 2017 and November 2023. Clinical characteristics and follow-up outcomes were collected for analysis. Results This study revealed 774 cases of brucellosis and 14 cases of BE, with an overall incidence rate of 1.88%. Most of the patients were male (71.43%) and lived in areas where brucellosis is common. Patients ranged in age from 26 to 68 years. Common symptoms reported among patients included chest tightness and fatigue, and a significant portion also presented with congestive heart failure. Most patients exhibited normal white blood cell counts (WBC) but had elevated levels of C-reactive protein (CRP). Transthoracic ultrasound (TTE) revealed cardiac valve vegetation in all patients, along with positive blood cultures. Six patients (42.86%) completed heart surgery, and ten (71.43%) completed anti-infection treatment. Six patients died, five of whom did not undergo surgery. The other patient with Marfan syndrome died after surgery. Sex, WBC count, neutrophil (NEUT) and total bilirubin (TBIL) were significant factors associated with regression in BE patients (P < 0.05) according to univariate analysis. Conclusions Patients with BE in Kashi have a severe clinical presentation at diagnosis, but early detection with improved cardiac ultrasound and aggressive treatment can improve the prognosis.